Sorotan Perkembangan Projek Etika Global: Kajian Terhadap Yayasan Etika Global (Global Ethic Foundation) - Che Nordin, Mohd Khairul Naim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2013)
Global ethic is an idea that claims an existence of one basic morality shared among people regardless of their race and religion since the beginning of humanity. It is founded on treatment among people that is humane and fair. From this foundation, the idea is elaborated into some attributes and criteria that form the moral framework that is collectively named as global ethic. To spread the idea, some activities are done under the Global Ethic Projects. This paper will review on the development of an organization that is directly related to Global Ethic Projects which is Global Ethic Foundation. It will also examine activities and programs held, as well as scrutinize the long-term planning of the organization in order to introduce global ethic to the world. The discourse will then be concluded with a summary on the current position of global ethic.